Dismissal Protection and Worker Flows in Small Establishments - Thomas K. Bauer; Stefan Bender; Holger Bonin (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2004)
Based on a large employer-employee matched data set, the paper investigates the effects of variable enforcement of German dismissal protection legislation on the employment dynamics in small establishments. Specifically, using a difference-in-differences approach, we study the effect of changes in the threshold scale exempting small establishments from dismissal protection provisions on worker flows. In contrast to the predictions of the theory, our results indicate that there are no statistically significant effects of the dismissal protection legislation on worker turnover.
Keywords: J58; J23; J21; 330; Employment Protection; Linked-Employer-Employee Data Set; Difference-in-Differences; Kündigungsschutz; Klein- und Mittelunternehmen; Arbeitsmobilität; Schätzung; Deutschland